Crystallization of a Two‐Dimensional Hydrogen‐Bonded Molecular Assembly: Evolution of the Local Structure Resolved by Atomic Force Microscopy. Issue 36 (28th July 2017) - Patera, Laerte L.; Liu, Xunshan; Mosso, Nico; Decurtins, Silvio; Liu, Shi‐Xia; Repp, Jascha
Abstract: Structures of the aromatic N‐heterocyclic hexaazatriphenylene (HAT) molecular synthon obtained by surface‐assisted self‐assembly were analyzed with sub‐Å resolution by means of noncontact atomic force microscopy (nc‐AFM), both in the kinetically trapped amorphous state and in the thermodynamically stable crystalline phase. These results reveal how the crystallization governs the length scale of the network order for non‐flexible molecular species without affecting the local bonding schemes. The capability of nc‐AFM to accurately resolve structural relaxations will be highly relevant for the characterization of vitreous two‐dimensional supramolecular materials. Abstract : Amorphous–crystalline transitions : The structure of a two‐dimensional hydrogen‐bonded amorphous film was revealed by means of noncontact atomic force microscopy. The resolution of the self‐assembly configurations in the disordered state allowed for a direct comparison with the bonding motifs found upon transition to the crystalline phase, shedding light on the crystallization process in organic self‐assemblies.